2004
DOI: 10.1093/bja/aeh050
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of early treatment with propofol on endotoxin-induced acute lung injury in rats

Abstract: These findings indicate that early administration of propofol may provide protective effects against endotoxin-induced acute lung injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 8 publications
4
35
0
Order By: Relevance
“…Loss of pulmonary barrier function is commonly seen as one of the most important features of ALI [32,33,34,35,36,37,38,39,40,41]. Numerous studies showed that indirect lung injury leading to ALI is commonly caused by extrapulmonary foci such as peritonitis, pancreatitis, trauma, massive transfusions or major surgery [18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Loss of pulmonary barrier function is commonly seen as one of the most important features of ALI [32,33,34,35,36,37,38,39,40,41]. Numerous studies showed that indirect lung injury leading to ALI is commonly caused by extrapulmonary foci such as peritonitis, pancreatitis, trauma, massive transfusions or major surgery [18,19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…This dosage of LPS was used in our previous studies 26 and by others. 27,28 At different time points (0, 2, 4, 8, and 12 h (n ¼ 7)), the animals were killed; blood and liver tissue were taken for analytical examination. All animals received humane care according to the criteria outlined in the 'Guide for the Care and Use of Laboratory Animals' prepared by the National Academy of Sciences and published by the National Institutes of Health (NIH publication 86-23 revised 1985).…”
Section: Materials and Methods Endotoxic Shockmentioning
confidence: 99%
“…In studies on endothelial cells, propofol has been reported to protect endothelial cells against the toxicity of peroxynitrite [13]. Recently, our studies have also shown propofol signifi cantly reduced endotoxin-induced peroxynitrite, and provided protective effects on endotoxin-induced acute lung injury and microvascular permeability in rats [14].…”
Section: Introductionmentioning
confidence: 71%
“…Our previous studies revealed that, in an endotoxin model, propofol signifi cantly attenuated LPS-enhanced expression of lung peroxynitrite and iNOSmRNA [14]. Studies in vitro also have reported that propofol protects endothelial cells against the toxicity of peroxynitrite [22,23] and reduces peroxynitrite in bronchial cells exposed to NO [12].…”
Section: Discussionmentioning
confidence: 93%